2017
DOI: 10.1186/s40168-017-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic cyst fluid harbors a unique microbiome

Abstract: BackgroundIt is clear that specific intestinal bacteria are involved in the development of different premalignant conditions along the gastrointestinal tract. An analysis of the microbial constituents in the context of pancreatic cystic lesions has, however, as yet not been performed. This consideration prompted us to explore whether endoscopically obtained pancreatic cyst fluids (PCF) contain bacterial DNA and to determine the genera of bacteria present in such material.MethodsTotal DNA was isolated from 69 P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(57 citation statements)
references
References 34 publications
1
55
1
Order By: Relevance
“…were also extremely high in two RIH subject. In a separate study, 408 genera of bacteria were identified in pancreatic cyst fluids obtained from patients through endoscopy (14); many of the taxa found in pancreatic cysts were similar to those in tissue del Castillo et al…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…were also extremely high in two RIH subject. In a separate study, 408 genera of bacteria were identified in pancreatic cyst fluids obtained from patients through endoscopy (14); many of the taxa found in pancreatic cysts were similar to those in tissue del Castillo et al…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have investigated the presence of specific bacterial DNA in the pancreatic tissue of pancreatic cancer subjects, namely species of Helicobacter (11) and Fusobacterium (12). The most comprehensive molecular microbiome studies to date reported the presence of a diverse bacterial populations in fluids collected from the bile duct, pancreas, and jejunum of subjects undergoing pancreaticoduodenectomy (13), and in pancreatic cyst fluid removed endoscopically from pancreatic cysts (14). In mice, bacteria have been shown to translocate from the mouth to the pancreas, and germfree mice have reduced progression of pancreatic ductal adenocarcinoma (15).…”
Section: Introductionmentioning
confidence: 99%
“…In a study of patients with pancreatic cystic lesions that were drained endoscopically, Li et al . also found intestinal bacterial strains, such as Bacteroides spp., E. coli and Shigella spp., to be present in cyst fluid.…”
Section: Discussionmentioning
confidence: 99%
“…6971 Bacteria are also detected in pancreatic cyst fluids including cysts associated with IPMN as well as non-neoplastic cysts, but the significance of these bacteria is not clear. 72 Despite these intriguing studies, the evidence that bacteria within the pancreas contributes to human pancreatic cancer pathogenesis is still limited.…”
Section: Introductionmentioning
confidence: 99%